Los corales (anthozoa e hidrozoa) de la ensenada de granate, pequeña bahía al, este de santa marta, colombia (1975)
The Ensenada Granate takes a special position within all the bays joining eastward to Santa Marta. Whereas the coral Tubastrea tenuilamellosa couldn't be pointed out in any of the other bays, it covers in the Ensenada Granate about 90 m2 of a rock-cave of the coast. Because of this individuality this bay will be described in this paper.  Twenty six different species of corals could be found and described in a measured underwater-profile. To get a survey of all the living corals of this bay, its western and eastern part was thoroughly searched, too, for proving the species. Ten other species could he found there. They are marked with ** in the list of species.